PELATIHAN TEKNIK PEMANTAUAN SAMPAH LAUT DI KAWASAN WISATA PANTAI SALIPER ATE, KABUPATEN SUMBAWA - Baiq Hilda Astriana; Mahardika Rizki Himawan; Aryan Perdana Putra (Universitas Mataram, 2022)
Saliper Ate Beach is one of the beaches located in Sumbawa Regency which has been a tourism destination for local people. The existence of this beach is important for local people whose livelihood is relied on the area. However, day by day the condition of this beach is getting more worrying due to the presence of trash increasing uncontrollable. This condition leads to fewer visitors coming to Saliper Ate Beach. Despite the large amount of trash in this area, it is known that there has not been any effort from local government to monitor marine trash, especially trash in beach area. The purpose of this community service activity was to provide knowledge to the participants regarding beach trash monitoring technique. The method used in this activity was the provision of knowledge in the form of training. The selected participants came from students who were members of the Scouts and Saka Kalpataru, Sumbawa. This activity was also supported by the local government through the Environmental Service Agency of Sumbawa Regency. The training material provided in this training were an introduction to types of beach trash, sampling techniques, and marine trash identification technique. The result of this activity is that the participants have the ability and skills to independently monitor beach trash and obtain data on the types of waste that have been successfully collected. The result of this activity is also expected to be useful in supporting local government effort in formulating policy regarding marine trash management. Key words: Marine trash, monitoring, Saliper Ate, Sumbawa